A Precise Microfluidic Assay in Single‐Cell Profile for Screening of Transient Receptor Potential Channel Modulators. Issue 11 (19th April 2020) - Ai, Xiaoni; Wu, Yang; Lu, Wenbo; Zhang, Xinran; Zhao, Lin; Tu, Pengfei; Wang, KeWei; Jiang, Yong
Abstract: Transient receptor potential (TRP) channels are emerging drug targets, and TRP channel modulators possess therapeutic potential for many indications. However, there is a lack of intellectual and robust screening assays against TRP channels utilizing the least amount of compounds. Here, a precise microfluidic assay in single‐cell profile is developed for the screening of TRP channel modulators. The geometrically optimized microchip is designed for both trapping single cells and utilizing passive pumping for sequential media replacement with low shear stress. The microfluidic chip exhibits superior performance in screening, repeatable compound administration, and improved reproducibility. Using this screening platform, the false‐positive and negative rate of the commonly used Ca 2+ imaging is reduced from 76.2% to 4.8% and four coumarin derivatives isolated from Murraya species that inhibit TRP channels are identified. One coumarin derivative B‐304 reverses TRPA1‐mediated inflammatory pain in vivo. Taken together, the data demonstrate that the established microfluidic assay in single‐cell profile could be used for the screening of TRP channel modulators that may have therapeutic potential for the channelopathies. Abstract : A precise microfluidic assay in single‐cell profile for screening of transient receptor potential (TRP) channel modulators is developed. The single‐cell‐based screening strategy dramatically reduces false‐positive/negative results from 76.2% to 4.8% due to full consideration of single‐cell heterogeneity. Four novel coumarin derivatives are cherry‐picked to potently inhibit TRP channels. One of the positive hits, B‐304, reverses TRPA1‐mediated inflammatory pain in vivo.